2021
DOI: 10.3389/fped.2021.682672
|View full text |Cite
|
Sign up to set email alerts
|

Re-evaluating Renal Angina Index: An Authentic, Evidence-Based Instrument for Acute Kidney Injury Assessment: Critical Appraisal

Abstract: Background/Introduction: Renal angina index (RAI) used to calculate and accurately predict risk for the development of acute kidney injury (AKI) has been heavily explored. AKI is traditionally diagnosed by an increase in serum creatinine (SCr) concentration or oliguria, both of which are neither specific nor sensitive, especially among children. An RAI score may be calculated by combining objective signs of kidney dysfunction (such as SCr) and patient context, such as AKI risk factors, thus potentially serving… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 23 publications
1
8
0
Order By: Relevance
“…Recognizing patients at risk of developing AKI through the RAI may lead to implementing early preventive measures and decrease complications secondary to AKI, with a possible impact on associated morbidity and mortality, hospital stay, and costs. [20][21][22] The RAI helps reliably differentiate children who will respond to conservative treatment from those who will need specialized renal treatment. 4 Studies have shown that an RAI ≥ 8 is useful for recognizing children with serious AKI who may require continuous renal support.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Recognizing patients at risk of developing AKI through the RAI may lead to implementing early preventive measures and decrease complications secondary to AKI, with a possible impact on associated morbidity and mortality, hospital stay, and costs. [20][21][22] The RAI helps reliably differentiate children who will respond to conservative treatment from those who will need specialized renal treatment. 4 Studies have shown that an RAI ≥ 8 is useful for recognizing children with serious AKI who may require continuous renal support.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, it seems that adding certain plasma biomarkers to the RAI may improve its discriminatory ability 20–23 . Basu et al 21 found that adding metalloproteinase 8 and neutrophil elastase 2 (ELA-2) measurement to the RAI increased its predictive ability from an AUC of 0.80 to an AUC of 0.88.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, a higher RAI threshold (≥ 12 or ≥ 20) has been found to be more useful than RAI of ≥ 8 [19]. Recently, Raina et al [25] reported that predictive ability of RAI for AKI had a pooled sensitivity of 79.21%, specificity of 73.22% and negative predictive value of 94.83%, analyzed in 11,026 participants.…”
Section: Clinical Applicationmentioning
confidence: 99%
“…Early biomarkers based on the identi cation of structural injury have been proposed, but their application and availability at the patient's bedside in pediatric intensive care units present a series of validation and clinical context limitations [10][11][12][13][14][15]. In response to this need, the renal angina index (RAI) was introduced as an analogy to chest angina in acute myocardial infarction, serving as a tool for the early recognition of AKI in critically ill patients [16][17][18][19][20]. There is limited information regarding its use and applicability in pediatric intensive care units with moderate resources in Latin America.…”
Section: Introductionmentioning
confidence: 99%